Valores pessoais na atuação em conselhos municipais: o caso dos CMAS de Minas Gerais - Alves, Cleusimar Cardoso (2014)
Social Assistance Councils are mechanisms of deliberative participation, of social control, negotiation places for propositions and actions in order to benefit many people and also to deepen democracy. They deal with decisions and actions that affect a whole community, being able to contribute to diminish the social inequality of a place. The public authority along with civil society considers, accompanies, evaluates, and presents measures for managing the social welfare policies in such segments. Based on that, the role of counselors is important and that discussion about the human values ​​that guides their actions may constitute an important tool to analyze and reflect on the axiological priorities that guide their behavior in the Council activities, considering that such values ​​are among the variables that influence the position chosen on those areas when dealing, for instance, with issues such as social participation and management of financial resources. Considering that, the main aim of the study was to discuss the motivational types of human values ​​that are priority among the Social Assistance Councils acting in the State of Minas Gerais. Such proposal was supported by the theory of basic human values ​​by Schwartz (2006) that describes a set of individual needs, identifying ten motivational types of values​​ as follows: Power, Achievement, Hedonism, Stimulation, Self-direction, Universalism, Benevolence, Tradition, Conformity and Security. This exploratory and descriptive research, based on a quantitative approach, used as an instrument of data collection the Portrait Values ​​Questionnaire - PQ-21 (LOMBARDI et al, 2010) and a social-demographic form. The probabilistic sample was composed of 204 representatives of the Municipal Councils from Minas Gerais State. The results showed that the motivational types of values’ hierarchy identified among the participantes of the study was: Benevolence, Universalism, and Self-direction, followed by Tradition, Security, and Conformity. The first two, which integrate the self-transcendence dimension, are in the first place when it comes to the respondents’ values priority, contributing to explain their commitment in getting engaged in activities favouring the social development and their roles in the activities accomplished. Also, Tradition, Security and Conformity values indicate a trend toward the preservation of traditional practices, resistance to change and acceptance and maintenance of the status quo. Along with that, the importance attributed to the values ​​of Self-direction was supported towards affirmation of their own ideas despite the collective ones. Thus, in general, the motivational types of values’ hierarchy identified among the Counselors may contribute to explore the potentialities of the Social Assistance Councils and achieve the democratic social control. However, the conservatism observed may difficult the struggle for collective rights, social justice, participation and deliberation equity. Other considerations, such as limits and contributions of the study are discussed.